Effective degradation of COVID-19 related drugs by biochar-supported red mud catalyst activated persulfate process: Mechanism and pathway. (15th March 2022) - Guo, Ziwei; Zhang, Yue; Gan, Shuchai; He, Huan; Cai, Nan; Xu, Jingwei; Guo, Pengran; Chen, Bo; Pan, Xuejun
Abstract: With the global spread of the COVID-19 pandemic, the water pollution caused by extensive production and application of COVID-19 related drugs has aroused growing attention. Herein, a novel biochar-supported red mud catalyst (RM-BC) containing abundant free hydroxyl groups was synthesized. The RM-BC activated persulfate process was firstly put forward to degrade COVID-19 related drugs, including arbidol (ARB), chloroquine phosphate, hydroxychloroquine sulfate, and acyclovir. Highly effective removal of these pharmaceuticals was achieved and even 100% of ARB was removed within 12 min at optimum conditions. Mechanism study indicated that SO4 − and HO were the predominant radicals, and these radicals were responsible for the formation of DMPOX in electron spin resonance experiments. Fe species (Fe 0 and Fe3 O4 ) and oxygen-containing functional groups in RM-BC played crucial roles in the elimination of ARB. Effects of degradation conditions and several common water matrices were also investigated. Finally, the degradation products of ARB were identified by Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) and possible degradation pathways were proposed. This study demonstrated that RM-BC/PS system would have great potential for the removal of COVID-19 related drug residues in water by the catalyst synthesized from the solid waste. Graphical abstract: Image 1 Highlights: A novel RM-BC catalyst containing abundant free OH groups was synthesized. RM-BC/PS system was firstly applied to remove COVID-19 drugs with high performance. Fe species and oxygen-containing functional groups in RM-BC played crucial roles. SO4 . − and HO were the main radicals responsible for the degradation of arbidol. The degradation pathway of ARB was proposed based on the FT-ICR-MS analysis.